Contemporaneous and lagged 𝑅2 decomposed connectedness approach: New evidence from the energy futures market - Balli F; Balli HO; Dang THN; Gabauer D (Elsevier Inc, 2023)
In this study, we investigate the return propagation mechanism across six energy futures, namely, Crude Oil, Heating Oil, Gasoline, Natural Gas, Kerosene, and Propane ranging from November 21st, 2014 until April 6th, 2023 by using a novel R2 decomposed connectedness approach. This framework allows to efficiently decompose connectedness measures into contemporaneous and lagged components. We find that the dynamic total connectedness is heterogeneous over time and economic-event dependent. Furthermore, the empirical results highlight that the contemporaneous effects are more pronounced on average while a significant amount of lagged spillovers occur in the case of Kerosene and Propane. We find that Heating Oil is the main net transmitter of shocks followed by Gasoline and Crude Oil while the main net receiver of shocks is Kerosene followed by Propane and Natural Gas. Finally, robust R2 connectedness measures are provided.
Keywords: Energy futures; Dynamic connectedness; Contemporaneous connectedness; Lagged connectedness